مقارنة الأساليب المستخدمة في تحديد عدد المركبات الرئيسية مع التطبيق العملي - العزاوي, دجلة ابراهيم; عبد القادر, زينة ياوز (Journal of Economics and Administrative Sciences, 2007)
The principal components analysis is used in analyzing many economic and social phenomena; and one of them is related to a large group in our society who are the university instructors. This phenomenon is the delay occurred in getting university instructor to his next scientific title. And as the determination of the principal components number inside the principal components depends on using many methods, we have compared between three of these methods that are: (BARTLETT, SCREE DIAGRAM, JOLLIFFE).     We concluded that JOLLIFFE method was the best one in analyzing the studying phenomenon data among these three methods, we found the most distinguishing factors effecting on the phenomenon was (the number of the lectures the university instructor has, the administrative routine, the entertainment activities, family situation, shortage in academic staff, pages number, the use of the internet and the political attitude).     So, we should begin with treating these factors as a first step for motivating university instructor to develop his thinking capabilities